Study of Some Morphometric Variables Using of Digital Elevation Models (DEM) of Wadi Habboun - Libya - AlKhboli, Mhi eldin Mohammed; Mostafa, Ashraf Mohamed; Ahmed, Saif al - Islam Mohammed (Al-Mukhtar Journal of Sciences, 2018)
The Habboun Valley is considered one of the valleys in Al-Jabal Al-Akhdar area, Libya, with an intensive agricultural activity. This study was carried out with the aim of identifying some of the morphometric properties of the valley, as well as building a spatial-digital database of the watershed to support and serve decision makers using DEM data. The topographic analysis was carried out for the study area and the boundaries of the Wadi Habboun watershed were determined and separated from the rest of the surrounding catchments. The morphometric analysis of the valley and its watershed was conducted to determine its different characteristics (area, Perimeter, the length of the watercourse, the slope of the stream). It showed that the total area of ​​the catchment is 34.2792 km2 and that it contains 37 Sub-catchment. The area of ​​these catchments ranged between 0.0324 to 2.65 km2. The length of the catchment is about 12.53 Km and its width is 2.74 Km and its perimeter is 43.74 Km. It tends to elongate in general and appears in the shape of triangle summit in the direction of the sea, while characteristics of the topography showed that it is a flat plank in its southern part, where agricultural activity is widespread, while it is highly concentrated in the northern part which occupied mostly with Mediterranean forests. The results of the analysis of the identification network showed that it contains 37 waterways and their total length reached 41.94 km and the length of the main stream of the 15.91 Km, as well as the streams of the basin straight and this means that the water reaches downstream in a short period of time and the frequency of the waterways is low and thus, reduces the chances of runoff within the valleys.